Initial Coefficient Bounds for Bi-Close-to-Convex Classes of n-Fold-Symmetric Bi-Univalent Functions - P. Gurusamy; M. Çağlar; L. I. Cotirla; S. Sivasubramanian (Axioms)
In this article, the strong class of bi-close-to-convex functions of order <semantics>α</semantics> and <semantics>β</semantics> in n-fold symmetric bi-univalent functions, which is the subclass of <semantics>σ</semantics>, is introduced. The upper bound value for <semantics><mfenced separators="" open="|" close="|">an+1</mfenced></semantics>, <semantics><mfenced separators="" open="|" close="|">a2n+1</mfenced></semantics> for functions in these classes are obtained. Moreover, the Fekete–Szegö relation for our classes of functions are established.